Effects of whole body vibration on pulmonary function, functional exercise capacity and quality of life in people with chronic obstructive pulmonary disease: a systematic review. (May 2016) - Yang, Xiaotian; Zhou, Yujing; Wang, Pu; He, Chengqi; He, Hongchen
Objective: To examine the effect of whole-body vibration in enhancing pulmonary function, functional exercise capacity and quality of life in people with chronic obstructive pulmonary disease and examine its safety. Method: Randomized controlled trials examining the effects of whole body vibration among people with chronic obstructive pulmonary disease were identified by two independent researchers. Articles were excluded if they were studies on people with other primary diagnosis, abstracts published in the conferences or books. PEDro scale was used to assess the methodological quality of the selected studies. We evaluated the level of evidence by using the GRADE approach. The results were extracted by two researchers and confirmed by the third researcher if disagreement existed. Data source: Sources included Cochrane Central Register of Controlled Trials, PubMed, CINAHL, EMBASE, PEDro, AMED, PsycINFO, ClinicalTrials.gov, Current Controlled Trials and reference lists of all relevant articles. Result: Four studies involving 206 participants were included in this systematic review. Methodological quality was rated as good for two studies. No great benefits on pulmonary function were found in whole body vibration treatment group. Two studies showed that quality of life was improved in people with chronic obstructive pulmonary disease. Whole body vibration led to significant improvements in functional exercise capacity measured with six minutes walking test. Nearly no adverse events were observed. Conclusion: Whole body vibration may improve functional exercise capacity and quality of life in people with chronic obstructive pulmonary disease. There was insufficient evidence to prove the effects of whole body vibration on pulmonary function.